Efficacy of herbicides on performance of chickpea (Cicer arietinum) in western Rajasthan - JAIN, L K; PAREWA, H P (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted from winter (rabi) season 2017–18 to winter (rabi) season 2020–21 at the research farm of College of Agriculture, Sumerpur, Pali, Rajasthan to find out the efficacy of herbicides in chickpea (Cicer arietinum L.) on sandy loam soils of western Rajasthan. The experiment comprised of 8 treatments with 4 replications in randomized block design (RBD) using cultivar RSG 974. The application of pendimethalin 30 ec @750 g/ha as pre-emergence (PE) recorded mean maximum seed yield of 15.02 q/ha followed by PE application of metalachlor 50 ec @1000 g/ha (12.52 q/ha) and were significantly superior over rest of herbicidal treatments. A similar trend was also found in weed parameters, growth and yield attributes under study. The mean maximum net returns (49112 `/ha) and a benefit to cost ratio (2.19) was recorded with pendimethalin 30 ec @750 g/ha as pre-emergence followed by treatment metalachlor 50 ec @1000 g/ha as pre-emergence (1.95) as against minimum in weedy check (0.89) during study period. Although, hoeing twice at 25 and 40 DAS gave higher seed yield (17.69 q/ha) and significantly superior over rest of treatments except in net return and B:C ratio.